Tahfiz Students’ Experiences in Memorizing the Qur’an: Unveiling Their Motivating Factors and Challenges - Nik Abdullah, Nik Md Saiful Azizi; Mohd Sabbri, Fathiyah Solehah; Muhammad Isa, Rabi’atul Athirah (IIUM Journal of Educational Studies, 2021)
This qualitative case study explores the factors behind Tahfiz secondary school students’ motivation to undertake the challenging task of memorizing the Qur’an and the challenges they experienced. The participants were six (6) Tahfiz students (three boys and three girls), aged between 15 and 17, who were enrolled in the Tahfiz Al-Qur’an program in two public secondary schools in Gombak and Bangi. The participants were selected by their teachers through purposeful sampling and had been engaged in Qur’an memorization for at least 2 years at the onset of the study. In-depth, semi-structured one-on-one interviews were conducted to examine their views about the factors that motivated them to memorize the Qur’an and the difficulties they faced. The findings pointed to three distinct categories of motivating factors: the students themselves, teachers and parents. In particular, parental guidance and advice were the most influential elements in students’ motivation to memorize the Qur’an. Among the challenges faced were time constraint, inability to remember verses, strict disciplinary rules and external noise that made the memorizing task difficult. In general, this study has shown the instrumental role of motivation in influencing Tahfiz students’ memorization of the Qur’an.